Value Chain Analysis on Pigmented Rice: A Case Study in Sleman Regency, Special Region of Yogyakarta, Indonesia - Kilana Putri Anindita; Dyah Ismoyowati; Endy Suwondo (agriTECH, 2019)
White rice has become the main source of carbohydrates, but in the last few years, red and black rice are getting more popular. Red and black rice can be an alternative food for people who wish to reduce the risk of diabetics due to its low glycemic index. Pigmented rice demand in Yogyakarta is continuously increasing. However, farmers are reluctant to plant pigmented rice because of their lower yields. Value chain analysis on pigmented rice is performed to provide the condition of the business’ performance for farmers who are not willing to work on pigmented rice yet. The objective of this study was to identify the main activities and to measure the performance of the value chain. The value chain performance was measured by calculating profit, marketing margin, and farmer’s share. In the business of pigmented rice nowadays, there are 5 actors involved, i.e. farmer, farmers group, association of farmers groups, distributor, and retailer. These five actors formed 5 value chains for red rice and 4 value chains for black rice. The main activities were cultivating, cropping, milling, sorting out, packing, and selling. The performance of the pigmented rice was as follows: on the red rice value chain, farmers earned the highest profit in each chain, except on the chain where the association of farmers groups was involved. The largest marketing margin was found on the farmer – association of farmer groups – retailer – end-user consumer chain. On the black rice value chain, farmers earned the highest profit in each chain, except on the chain where the farmers group was involved. The largest marketing margin found on the farmer – farmers group – distributor – retailer – end-user consumer chain. For both the red and the black rice value chain, the farmer’s highest share was obtained on the farmers – distributor – end-user consumer chain.